Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
3 Answers
- 9 years agoFavorite Answer
Knowledge of logarithm is needed to solve this equation.
3^(x/2+1) = 12.2
Add lg at both sides,
lg 3^(x/2+1) = lg 12.2
(x/2+1) lg 3 = lg 12.2
(x/2+1) = lg 12.2/lg 3
(x/2+1) = 2.2769
x/3 = 2.2769
x = 2.2769*3
= 6.8307
- Jeff AaronLv 79 years ago
3^((x/2) + 1) = 12.2
(x/2) + 1 = log (base 3) of 12.2
x/2 = (log (base 3) of 12.2) - 1
x = 2*((log (base 3) of 12.2) - 1)
x =~ 2.55381
Or did you mean:
3^(x/(2+1)) = 12.2
3^(x/3) = 12.2
x/3 = log (base 3) of 12.2
x = 3*(log (base 3) of 12.2)
x =~ 6.83
- d/dx+d/dy+d/dzLv 69 years ago
let C = 12.2
then with some rearranging you get
x = 2*(ln(C)/ln(3)-1)
x = 2.28